Cross-border cooperation between Slovenia and Croatia in Istria after 1991 - Pipan, Primož (Acta geographica Slovenica, 2007)
The paper discusses the impact of the international border established in 1991 on cross-border cooperation. It focuses on the impact of the Agreement between the Republic of Slovenia and the Republic of Croatia on Border Traffic and Cooperation (SOPS) and introduction of the Schengen Agreement as a result of Slovene accession to the EU. The paper highlights the effect of the border on local population. It uses a number of interviews to present the people's attitude to the new realities of the border while at the same time determining the impact of the border on local development and the organisation of Italian national minority in Istria. In conclusion, the paper outlines the three areas formed along the border with regard to the changes in the intensity of cross-border cooperation and the related local development. Finally, the paper attempts to indicate the future development of the area in the context of cross-border cooperation along the EU's external border.
Keywords: politična geografija; obmejna območja; obmejno sodelovanje; Istra; Istria; Slovenia; Slovenija; Croatia; Hrvaška